1997
DOI: 10.1046/j.1365-2265.1997.d01-1749.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebrovascular mortality in patients with hypopituitarism

Abstract: The increased cerebrovascular mortality may be due to GH deficiency, or to long-term lack or inadequacy of substitution for other pituitary hormones. The observations that an early onset of pituitary insufficiency and female sex are predictors for a high risk for cerebrovascular mortality merit particular attention when treating this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
348
3
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(377 citation statements)
references
References 19 publications
16
348
3
10
Order By: Relevance
“…Epidemiological studies have shown that this abdominal obesity is a risk factor for development of metabolic abnormalities leading to cardiovascular complications [4,5]. In studies in Japanese adult patients with GHD it has been shown that there is an increased risk of cardio-and cerebro-vascular morbidity and mortality compared to the normal population [6][7][8], similar to that previously shown in Caucasian patients [5,[9][10][11].…”
supporting
confidence: 64%
“…Epidemiological studies have shown that this abdominal obesity is a risk factor for development of metabolic abnormalities leading to cardiovascular complications [4,5]. In studies in Japanese adult patients with GHD it has been shown that there is an increased risk of cardio-and cerebro-vascular morbidity and mortality compared to the normal population [6][7][8], similar to that previously shown in Caucasian patients [5,[9][10][11].…”
supporting
confidence: 64%
“…16,25,26,30 ± 32 There is no clear explanation for this observation, although GH de®ciency has been proposed as the most possible explanation. 18,19 Our hypopituitary patients had signi®cantly higher triglyceride, total and LDL cholesterol and signi®cantly lower HDL cholesterol concentrations. This lipid pro®le constitutes a vascular risk.…”
Section: Discussionmentioning
confidence: 67%
“…When given conventional replacement therapy, patients with hypopituitarism show an increased mortality from cardiovascular disease 18,19,29 and increased prevalence of cardiovascular risk factors. 16,25,26,30 ± 32 There is no clear explanation for this observation, although GH de®ciency has been proposed as the most possible explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacientes com hipopituitarismo apresentam aumento da mortalidade quando comparados à população geral (4)(5)(6)(7)(8)(9). Alguns estudos demonstraram aumento de mortalidade por causa de doenças cardiovasculares (4,5,8,9).…”
unclassified